THE DEVELOPMENT OF ENGLISH READING COMPREHENSION ABILITY BASED ON LOCAL CONTEXT READING MATERIALS WITH SCAFFOLDING TECHNIQUE OF UNDERGRADUATE STUDENTS - Rotchu, Phananoi (Journal of MCU Nakhondhat, 2020)
The objectives of this research article were to study the English reading comprehension ability, and the motivation of undergraduate students towards the use of Local context material with scaffolding technique. The samples were 30 students of undergraduate students, Suratthani Rajabhat University by simple random sampling. The instruments of research consisted of lesson plans, English reading test and questionnaire. Data were analyzed by using mean, standard deviation, and t - test for dependent. The results of the research showed that the reading comprehension ability after using Local context material with scaffolding technique was higher than that before significantly at the .05 level and the students’ motivation towards the use of Local context material with scaffolding technique was at a high level in overall and each aspect the useful of reading English ( = 4.3, S.D. = .0.51) to be determined to learn ( = 4.49, S.D. = .0.52) successful learner ( = 4.42, S.D. =.0.60) .Local context material were as follows 1) Local Foods 2) Local Wisdom3) Places of interest) 4) Way of Life 5) Significant people) 6) Festival 7) Costume 8) Southern Show